Phase Evolution of Ti3SiC2 Annealing in Vacuum at Elevated Temperatures. Issue 3 (8th March 2012) - Zeng, Junling; Ren, Shufang; Lu, Jinjun
<x xml:space="preserve">Abstract</x> The thermal decomposition of Ti3SiC2 in vacuum furnace up to 1500°C has been investigated. The results show that the mild decomposition of Ti3SiC2 commences at 1300°C and the higher the holding temperature, the larger the volatilization of Si atoms. The Ti3SiC2 decomposition occurs simultaneously on the surface and in the bulk. Four phases coexist at 1400°C and 1450°C and the Ti5Si3Cx phase appears in the bulk and/or surface. Diffusion distance, rate, and volatilization of Si contribute to the porous structure and the presence of Ti5Si3Cx. The evolution of furnace pressure reflects the decomposition kinetics of Ti3SiC2.